2023
DOI: 10.1093/ofid/ofad165
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Screening Intensity in Terms of Reducing Prevalence or Increasing Selection Pressure for the Emergence of Resistant Gonorrhea: A Modeling Study of Men Who Have Sex With Men in Belgium

Abstract: Background Neisseria gonorrhoeae (NG) has developed antibiotic resistance (AMR) to multiple classes of antibiotics. While treatment of symptomatic NG in groups, like men who have sex with men (MSM) is crucial, screening programs targeting asymptomatic NG cases may contribute to excessive antibiotic exposure of the population and thus to the emergence of gonococcal AMR. Our primary aim was to assess if intense screening could promote AMR in NG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…lactis IL1403 ( n = 1) (Table 2). In Belgium, resistance to gonococcal azithromycin has increased from 0.2% to 18.6% over the past 8 years, despite the use of dual therapy, i.e., ceftriaxone and azithromycin ( 49 ). Therefore, in this study, the WHO-P N. gonorrhoeae isolate was used in the initial in vitro screening and in vivo experiments due to its susceptibility to ceftriaxone (0.004 µg/mL) and resistance to azithromycin (4 µg/mL), as determined by the European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…lactis IL1403 ( n = 1) (Table 2). In Belgium, resistance to gonococcal azithromycin has increased from 0.2% to 18.6% over the past 8 years, despite the use of dual therapy, i.e., ceftriaxone and azithromycin ( 49 ). Therefore, in this study, the WHO-P N. gonorrhoeae isolate was used in the initial in vitro screening and in vivo experiments due to its susceptibility to ceftriaxone (0.004 µg/mL) and resistance to azithromycin (4 µg/mL), as determined by the European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…nonpathogenic Neisseria species) [90 ▪ ,91,92], and microbiome [93,94]. Although reducing screening can improve antimicrobial stewardship [95 ▪ ], this may lead to some fear and concerns from the MSM community. An Australian qualitative study among 13 MSM using HIV PrEP found that they were aware of the concern of antibiotic resistance but they would still want the 3-monthly asymptomatic STI screening to ensure their safety and there was a fear of the rise of STIs in their community if they were screened less frequently [96 ▪ ].…”
Section: Screening For Oropharyngeal Infectionsmentioning
confidence: 99%
“…Several modeling studies have described the transmission of CT and NG among MSM [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], which cluster in a few Western countries, mainly from the US [ 9 , 13 , 14 , 19 , 25 , 26 , 27 , 28 , 35 , 36 ] and Australia [ 18 , 22 , 23 , 24 , 32 , 40 , 41 , 42 , 43 ]. In Europe, notable modeling studies have been conducted in the UK [ 31 , …”
Section: Introductionmentioning
confidence: 99%
“…In Europe, notable modeling studies have been conducted in the UK [ 31 , 37 , 38 , 45 ] and The Netherlands [ 17 , 29 , 30 , 33 , 39 , 44 ], with few papers from France [ 34 ], Belgium [ 8 , 16 ] and Switzerland [ 20 , 21 ]. The majority of the published models from Europe are compartmental models, with only a hand-full of models using individual-based or network models [ 8 , 16 , 29 , 30 , 39 , 45 ]. While the usefulness of compartmental models is undeniable, they lack both the complexity of the transmission mechanisms of STIs and the fine-grain detail of individual characteristics that individual-based and network models exhibit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation